Surgical management of papillary thyroid carcinoma coexisting with Hashimoto’s disease: a single-center retrospective cohort study - Zhang, Dongdong; Wu, Jixiang; Chen, Lin (Frontiers in Endocrinology, 2024)
Background The mechanism and impact of Hashimoto’s disease (HT) in patients with papillary thyroid carcinoma (PTC) remains a subject of ongoing debate. The optimal extent of thyroid resection is also controversial in cases of low-risk PTC. Objective To investigate the clinical outcomes and prognoses associated with different extents of surgical resection in patients diagnosed with PTC coexisting with HT. Methods We retrospectively analyzed data on the clinical features and treatment outcomes of patients with PTC concomitant with HT who underwent lobectomy with isthmusectomy and those who underwent total thyroidectomy at Peking University International Hospital between December 2014 and August 2023. Results Twenty-one patients in group A underwent lobectomy with isthmusectomy and prophylactic central neck dissection, whereas twenty patients in group B underwent total thyroidectomy with prophylactic central lymph node (LN) dissection, except one who did not undergo LN dissection. Group A demonstrated shorter surgery time (105.75 min ± 29.35 vs. 158.81 min ± 42.01, p = 0.000), higher parathyroid hormone (PTH) levels on postoperative day 1 [26.96 pg/ml (20.25, 35.45) vs. 9.01 pg/ml (2.48, 10.93), p = 0.000] and a shorter postoperative hospital stay [2.95 d (2.0, 4.0) vs. 4.02 d (3.0, 5.0), p = 0.008] than those of group B, with statistically significant differences. Both groups exhibited similar recovery patterns in terms of PTH [32.10 pg/ml (22.05, 46.50) vs. 20.47 pg/ml (9.43, 34.03), p = 0.192] and serum calcium (2.37 mmol/L ± 0.06 vs. 2.29 mmol/L ± 0.19, p = 0.409) after 1 montsh following the surgery. According to the Kaplan-Meier curves, no significant difference in the 5-year disease-free survival rates were observed between patients in group A (100%) and group B (97.1%) (Log rank test: p = 0.420, Breslow test: p = 0.420). Conclusion Lobectomy with isthmusectomy and prophylactic central neck dissection is a safe and feasible treatment option for patients with low-risk PTC coexisting with HT. Clinical trial registration http://www.chictr.org.cn, identifier ChiCTR2300079115.